Peran Perpustakaan Dalam Meningkatkan Minat Baca Pemustaka Pada Dinas Perpustakaan Kota Samarinda - Nanik Pujiastuti dan Munawarah (Prodi Ilmu Administrasi Negara, 2018)
The purpose of this study is to determine the role of libraries inincreasing interest in library visitors at Dinas Perpustakaan KotaSamarinda and to know the services provided in increasing interest inreading the library visitors at Dinas Perpustakaan Kota Samarinda.The method used in this research is descriptive qualitative method. Thetechnique used is Purposive Sampling and Accidental Sampling technique. Inthis study, the authors also use survey research, interviews, anddocumentation in order to obtain data on the Role of Library in ImprovingReading Interest of Library Visitors at Dinas Perpustakaan Kota Samarinda.The results showed that some of the role of libraries in increasing theinterest of reading library visitors at the Dinas Perpustakaan KotaSamarinda hasn’t run smoothly, namely the availability of a completecollection of books and the provision of adequate facilities. As forsocialization activities and services to library visitors have been running, butnot maximized because of the obstacles.In conclusion, the role of the Library in Improving the Interest ofVisitors Library at the Dinas Perpustakaan Kota Samarinda is still notmaximal in the implementation of its activities, because constrained thelimited budget funds, wide working areas, and inadequate facilities.